2009
DOI: 10.1088/1126-6708/2009/03/084
|View full text |Cite
|
Sign up to set email alerts
|

Beyond η/s= 1/4π

Abstract: We use a low-energy effective description of gauge theory/string theory duality to argue that the Kovtun-Son-Starinets viscosity bound is generically violated in superconformal gauge theories with non-equal central charges c = a. We present new examples (of string theory constructions and of gauge theories) where the bound is violated in a controllable setting. We consider the comparison of results from AdS/CFT calculations to the QCD plasma in the context of this discussion.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
282
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(294 citation statements)
references
References 92 publications
8
282
2
Order By: Relevance
“…It has been verified that in certain charged black hole backgrounds, the charge parameter q e also contributes to the corrections to η/s [31,32,33,34,35,36]. However, it seems that our result does not have any dependence on q e .…”
Section: Gauss-bonnet Corrections To η/S At Finite Temperaturementioning
confidence: 54%
See 1 more Smart Citation
“…It has been verified that in certain charged black hole backgrounds, the charge parameter q e also contributes to the corrections to η/s [31,32,33,34,35,36]. However, it seems that our result does not have any dependence on q e .…”
Section: Gauss-bonnet Corrections To η/S At Finite Temperaturementioning
confidence: 54%
“…By evaluating the conserved flux at the horizon, we can easily check that 33) and thus, combining with the result (4.31), the real part of the conductivity is…”
Section: Conductivitymentioning
confidence: 88%
“…It was also initially suggested that this value is a bound, and the ratio can never become smaller. We now know that this is not true [4][5][6][7], see also [8,9], but in all controlled counter-examples the bound is violated at best by a numerical factor, and not in a parametric manner. Attempts to produce bigger violations lead to physically unacceptable situations, e.g., to causality violations, for example, see [10,11].…”
Section: Jhep10(2015)028mentioning
confidence: 96%
“…If the latter conditions are not met (1.1) may fail. For instance, once the 't Hooft coupling of the gauge theory or the rank of its gauge group are finite, the ratio (1.1) is corrected [22][23][24][25][26][27][28][29][30][31][32][33][34]. More recently, (1.1) has been shown to break down in non isotropic configurations which are described by two derivative theories of gravity [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%